2012
DOI: 10.1179/1743285512y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of pre-reduction of manganese ore by CO

Abstract: The degree of reduction of the higher oxides of manganese to the lowest oxide, MnO, achieved during the pre-reduction of manganese ore has a direct impact on the energy consumption for the subsequent smelting process. For ferruginous manganese ores, understanding the kinetics of pre-reduction is also useful for controlling the process parameters to optimise specific power consumption and maximise the metal recovery for upgrading by magnetic separation. The effects of reduction temperature, gas composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Previous studies have also observed that Comilog and Nchwaning ore reduce faster in CO-CO 2 atmospheres in smaller particle sizes. [2,16,22] Gao [11] observed no effect by changing the particle size between < 45 to 1000 lm when reducing a precalcined ore in CO-CO 2 atmosphere. This may suggest that the ores have a threshold value at which the kinetics are affected by the particle size.…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also observed that Comilog and Nchwaning ore reduce faster in CO-CO 2 atmospheres in smaller particle sizes. [2,16,22] Gao [11] observed no effect by changing the particle size between < 45 to 1000 lm when reducing a precalcined ore in CO-CO 2 atmosphere. This may suggest that the ores have a threshold value at which the kinetics are affected by the particle size.…”
Section: Observationsmentioning
confidence: 99%
“…On the other hand, these semi-oxidized ores often contains significant amount of iron oxides, which may reduce through sequence Fe 2 O 3 -Fe 3 O 4 -FeO-Fe. Several experimental studies have been reported regarding prereduction of manganese ores in CO-CO 2 atmosphere, both in isothermal [2,5,10,11] and non-isothermal [6,[12][13][14][15][16] temperature regimes. Non-isothermal studies have commonly been used to simulate the industrial furnace conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…8). In addition, according to the reports [33,34], it is the chemical reaction that controls the reduction of iron ore pellet at the temperature range of 550 °C to 750 °C. Therefore, reduction rates of reactions (1) -(3) are improved by the high temperature.…”
Section: Influences Of Carburizing Temperaturementioning
confidence: 99%
“…Manganese has been a critical element for the production of steels, batteries, fertilizer, non-ferrous alloys, catalysts, and pigment, etc. [1][2][3] Driven by the high crude steel production rate of China, global manganese resources have been mostly consumed by the country [4,5] for the production of manganese ferroalloy, which is produced by smelting with submerged electric arc furnaces (SAF) at a high energy cost [6][7][8][9]. Cheap and high-grade manganese ores have become scarce due to its continuous consumption.…”
Section: Introductionmentioning
confidence: 99%